Exploiting Spermidine N‑Hydroxycinnamoyltransferase Diversity and Substrate Promiscuity to Produce Various Trihydroxycinnamoyl Spermidines and Analogues in Engineered Yeast - Perrin, Jennifer; Kulagina, Natalja; Unlubayir, Marianne; Munsch, Thibaut; Carqueijeiro, Inês; Dugé de Bernonville, Thomas; De Craene, Johan-Owen; Clastre, Marc; St-Pierre, Benoit; Giglioli-Guivarc’h, Nathalie; Gagneul, David; Lanoue, Arnaud; et al. (ACS synthetic biology, 2021)
Trihydroxycinnamoyl spermidines (THCSpd) are plant specialized metabolites with promising pharmacological activities as antifungals, antibacterial, antiviral, and antidepressant drugs. However, their characterization and potential pharmaceutical exploitation are greatly impaired by the sourcing of these compounds, restricted to the pollen of core Eudicot plant species. In this work, we developed a precursor-directed biosynthesis of THCSpd in yeast using a dual enzymatic system based on 4-coumarate-CoA ligases (4CL) and spermidine N-hydroxycinnamoyltransferases (SHT). The system relies on the yeast endogenous spermidine pool and only requires hydroxycinnamic acids as exogenous precursors. By exploring 4CL isoforms and SHT diversity among plants, we have driven the production of 8 natural THCSpd, using single or mixed hydroxycinnamic acid precursors. Substrate promiscuities of 4CL and SHT were genuinely exploited to produce 8 new-to-nature THCSpd from exotic hydroxycinnamic and dihydrohydroxycinnamic acids, together with 3 new-to-nature THCSpd containing halogenated hydroxycinnamoyl moieties. In this work, we established a versatile and modular biotechnological production platform allowing the tailor-made THCSpd synthesis, constituting pioneer metabolic engineering for access to these valuable natural products.